Social class and gender patterning of insomnia symptoms and psychiatric distress: A 20-year prospective cohort study - Green, M; Espie, C; Benzeval, M (BioMed Central, 2014)
Background: Psychiatric distress and insomnia symptoms exhibit similar patterning by gender and socioeconomic position. Prospective evidence indicates a bi-directional relationship between psychiatric distress and insomnia symptoms so similarities in social patterning may not be coincidental. Treatment for insomnia can also improve distress outcomes. We investigate the extent to which the prospective patterning of distress over 20 years is associated with insomnia symptoms over that period.Methods: 999 respondents to the Twenty-07 Study had been followed for 20 years from approximately ages 36-57 (73.2% of the living baseline sample). Psychiatric distress was measured using the GHQ-12 at baseline and at 20-year follow-up. Gender and social class were ascertained at baseline. Insomnia symptoms were self-reported approximately every five years. Latent class analysis was used to classify patterns of insomnia symptoms over the 20 years. Structural Equation Models were used to assess how much of the social patterning of distress was associated with insomnia symptoms. Missing data was addressed with a combination of multiple-imputation and weighting.Results: Patterns of insomnia symptoms over 20 years were classified as either healthy, episodic, developing or chronic. Respondents from a manual social class were more likely to experience episodic, developing or chronic patterns than those from non-manual occupations but this was mostly explained by baseline psychiatric distress. People in manual occupations experiencing psychiatric distress however were particularly likely to experience chronic patterns of insomnia symptoms. Women were more likely to experience a developing pattern than men, independent of baseline distress. Psychiatric distress was more persistent over the 20 years for those in manual social classes and this effect disappeared when adjusting for insomnia symptoms. Irrespective of baseline symptoms, women, and especially those in a manual social class, were more likely than men to experience distress at age 57. This overall association for gender, but not the interaction with social class, was explained after adjusting for insomnia symptoms. Sensitivity analyses supported these findings.Conclusions: Gender and socioeconomic inequalities in psychiatric distress are strongly associated with inequalities in insomnia symptoms. Treatment of insomnia or measures to promote healthier sleeping may therefore help alleviate inequalities in psychiatric distress. © 2014 Green et al.; licensee BioMed Central Ltd.